Drought Stress Interacts With Powdery Mildew Infection in Tomato - Sunarti, Sri; Kissoudis, Christos; Van Der Hoek, Yannick; Van Der Schoot, Hanneke; Visser, Richard G. F.; Van Der Linden, C. Gerard; Van De Wiel, Clemens; Bai, Yuling (Frontiers in Plant Science, 2022)
Under field conditions, plants are often exposed to more than one stress factor at the same time, and therefore need to adapt to different combinations of stresses. Crosstalk between responses to abiotic and biotic stresses is known to occur, and the interaction between stress responses can be positive or negative. We studied the interaction of drought stress and powdery mildew (PM) infection in tomato using near-isogenic tomato lines (NILs) carrying the Ol-1, ol-2, or Ol-4 gene that confer resistance to tomato PM caused by Oidium neolycopersici. Our study demonstrated that drought-induced growth reduction was not further reduced by powdery mildew infection. Drought stress, however, decreased fungal infection in the susceptible genotype Moneymaker (MM) with fungal biomass tending to decrease further as the drought severity increased. Drought stress did not affect PM resistance levels of resistant NIL carrying ol-2 (a mutant of the tomato susceptibility Mlo gene) and Ol-4 (an NLR (nucleotide-binding site-LRR) R gene associated with a fast hypersensitivity response (HR), but tended to slightly decrease disease levels of NIL-Ol-1 (no gene characterized yet, associated with a slow HR following PM infection). At the molecular level, genes involved in ABA, salicylic acid and ethylene pathways were highly induced under combined stress indicating the involvement of ABA, SA and ethylene in the crosstalk between abiotic and biotic stress. Messenger RNA expression of the ABA-responsive dehydrin SlTAS14 was induced under drought and combined stress with highest induction under combined stress, and resistant NIL lines showing higher expression levels than MM. The expression of SlNCED (involved in ABA synthesis) was also upregulated under drought and highly induced under combined stress. Expression levels of pathogen responsive gene SlPR1 (indicator of salicylic acid pathway) and SlACS (involved in ethylene synthesis) were highly induced under powdery mildew infection in MM and the Ol-1 and was induced the most under combined stress in these lines. Taken together, these findings indicate that drought stress can interact with and influence PM infection in tomato in a resistance type-dependent manner. The role of hormonal signaling pathways in the crosstalk between drought stress and PM infection is further discussed.